Numbers do the Majic – Fast Tracking the Game (Global Business Management Review (GBMR), 2022)
Car travel is no more a luxury now-a-days in India and it is now the choice of a common man. It has become a necessity and many jobs get done faster and easier by moving in cars. To cater to the needs of people who can spend extra money for transport, but at the time, buying a car is not possible for them call taxi service has become a great rescuing factor. There are many options of different call taxis to choose from. As far as Call Taxi services are concerned even though the service provider name is popular, easy to recollect and in the top of mind recall, most of the people especially first time users and occasional users do not remember or recollect the phone number of the call taxi operator when needed. With the tariff and services offered are more or less the same among all the operators retaining a customer is a Herculean task for the call taxi operators. There is little scope for differentiation and the operators try to offer customized services and short term promotions to the customers to attract and avoid customer defection. The case can be analyzed from the following perspectives – New product launch, Market leader strategies, Services Marketing – Tangibilizing the intangibles, Advertisement message, Sales promotion techniques, Product Differentiation strategies.